The contemporary history play staging English and American pasts - Poore, Benjamin 1971- (Bloomsbury Publishing Plc, 2024)
"Something exciting is happening with the contemporary history play. New writing by playwrights such as Jackie Sibblies Drury, Samuel Adamson, Hannah Khalil, Cordelia Lynn, and Lucy Kirkwood, makes powerful theatrical use of the past, but does not fit into critics' familiar categories of historical drama. In this book, Benjamin Poore provides readers with tools to name and critically analyse these changes. The Contemporary History Play contends that many history plays are becoming more complex and layered in their aesthetic approaches, as playwrights work through the experience of being surrounded by numerous and varied forms of historical representation in the twenty-first century. For theatre scholars, this book offers a means of interpreting how new writing relies on the past and notions of historicity to generate meaning and resonance in the present. For playwrights and students of playwriting, the book is a guide to the history play's recent past, and to the state of the art: what techniques and formulas have been popular, the tropes that are widely used, and how artists have found ways of renewing or overturning established conventions."
Keywords: Geschichte 2000-2024; Historisches Drama; Englisch; Historical drama, English / History and criticism; Playscript; Theatre studies; Drama / History and criticism